Surgical Management of Intraocular Silicone Oil Microdroplet - Safi, Antoine; Wolfensberger, Thomas J. (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose Intraocular silicone oil microdroplets have been described after intravitreal injection of anti-VEGF agents packaged at a compound pharmacy. We present a case with the presence of an intraocular silicone oil microdroplet after a vitreoretinal operation using disposable instruments, and the surgical technique for its removal.Methods A 59-year-old patient who had been operated on for vitreous opacities using a disposable 27-g vitrectomy kit complained of a small round structure floating in the eye. It appeared a few days after surgery. The bubble was not present at all times and it disappeared for days on end. Clinical examination of the vitreous and retina during these uneventful periods was normal. The bubble reappeared intermittently without a link to any specific movement for some time but was again absent once the patient was examined. The physical properties of the mobile round lesion could be identified as lighter than aqueous humor, as it was described as being in the center of the visual field if the head was tilted forward.Results As the patient was very bothered by this bubble, a 23-g vitrectomy was performed. During deep indentation of the pars plana over 360 degrees, a tiny bubble of silicone oil could be found buried in the peripheral vitreous base, and controlled aspiration under deep indentation was performed. The patient has been without symptoms since the removal of the droplet and made an uneventful clinical recovery.Conclusion Microdroplets of silicone oil may be present in disposable vitreoretinal instruments and stay in the eye after surgery, causing a visual disturbance. The origin of these droplets may be linked to the plastic tubing of the instruments.
Keywords: vitreous; silicone oil; polydimethylsiloxane; microdroplet; floaters